Metodologija za izračun dnine delavca sekača v koncesijskih gozdovih v Sloveniji - Kavčič, Slavka (Gozdarski vestnik, 2011)
Forestry belongs to the occupational branches comprising also occupations whose forming of selling prices is based on costs instead on offer and demand.Felling of wood in concession forests whose management has been handed over to forest services on the basis of a concession contract by the state ranks among these occupations. This article suggests a methodology for forming full cost and selling price of a day wage for a logger felling wood in concession forests in Slovenia. Also the concrete costing of the selling price of a day wage for felling and the needed overhead rate of logger's hourly rate covering the indirect costs and profit were calculated on the basis of forest services' data for 2009 in accordance with the suggested method.
Keywords: forestry; gozdarstvo; sekači; stroški; gozdno gospodarstvo; poslovanje podjetja; koncesije; dobiček